Assessment of Fractional and Integer Order Models of Induction Motor Using MATLAB/Simulink - Girma Kassa Alitasb (Modelling and Simulation in Engineering)
The definition of derivatives and integrals of any real or complex order can be found in fractional calculus, which is an extension of ordinary calculus. Many real-world processes might be more accurately modeled by these fractional calculi. Flexibility and nonlocality are the two fundamental benefits of fractional derivatives. These derivatives, which are of fractional order, are more flexible than classical derivatives in how they might approach real data. Due to its applications in numerous domains, the fractional order model has grown in significance and popularity. The simulation results have been performed for three squirrel cage induction motors which have different parameter values. To perform fractional order calculus, the Fractional Order Modeling and Control (FOMCOM) toolbox has been added to MATLAB. To determine the value of the order of differentiation (α) that best represents the induction motor, speed and torque simulations for several orders of differentiation (α) were performed. According to the results of the speed and torque simulation, an integer order (α=1) model is the optimal representation of the induction motor. The main goal of this paper is to investigate which model, either integer or fractional order model, best represents an induction motor.